Numerical Simulation of Fracture Behavior of Brittle Solids under I/III Loading - Zhitao Zhang; Haijun Wang; Shuyang Yu (Advances in Civil Engineering)
This study used numerical analysis to carry out a large number of numerical model calculations based on a new semicircular bend (SCB) model. Instead of existing numerical computation methods (J-integral), the M-integral method was used to calculate the mixed mode fracture parameters (KI, KII, and KIII), investigate the influence of the geometry and material parameters on the fracture behavior under mixed mode I/III loading, and predict the fracture path. The results revealed that the limitations in the scope of the mixity parameter Me in the previous studies can be overcome to a certain extent. The range of Me was established under different Poisson ratios and can be used as a reference for actual material testing. The simulation path is in good agreement with the experimentally obtained fracture path, and the proposed method can be used to simulate the fracture path under mixed mode I/III loading.